Validity and Reliability of Research Instruments on the Effect of Motivation on Nurse Performance in Moderation with Nurse Credentials - Rio Dimas Sugiarta; Fitri Arofiati; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Instruments with indicators must match the variables to be observed and declared valid and reliable before being used for research. Work motivation variables and credential variables affect nurse performance. Credentials can moderate the effect of work motivation on nurse performance. The research objectives were then analyzed using internal validity and reliability conducted by experts and external reliability validity using a questionnaire filled out by research respondents about the effect of motivation on nurse performance in moderation with nurse credentials. This research used quantitative methods with a cross-sectional design. The research population consisted of 58 nurses and the chairman of the nursing committee served as the validator. The sampling technique was total sampling with 56 registered nurses as permanent employees and receiving credentials. The research instrument used a questionnaire. Analysis of the validity and reliability of the data used the SPSS application and Structural Equation Modeling (SEM) analysis with the PLS application. The research instrument influenced motivation on nurse performance moderately, with credentials declared valid and reliable.